Contextualization of Jihad in the Qur'an (Efforts to Find the Transcendental Hermeneutic Side of Fazlur Rahman's Double Movement) - Siti Aldasari Dwi Rohmawati Al-Murod; Maulidatus Saniyah; Khoirul Umami (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Contextual studies to understand the verses of the Qur'an are increasingly in demand by ulumul qur'an researchers today. One approach that is often applied in a Qur'anic study is Fazlur Rahman's double movement hermeneutic. This approach strongly emphasizes the socio-historical context of the revelation of the verse and also the conditions of the present oriented to the discovery of moral ideals. Thus, the purpose of the revelation will still be conveyed at any time. During this decade, the double movement hermeneutic approach has focused more on ethico-legal verses, namely verses that contain certain ethical, moral, social, and legal values. Furthermore, new interpretations are found in the form of legal products that adjust the content of the verse to the situation and conditions that are currently developing in society. In this article, several verses related to the concept of jihad will be analyzed, namely Surah al-Nisa' verse 95 and Surah al-Taubah verses 20 and 24. Of course, these verses are dissected using asba>b al-nuzu>l studies and historical studies that intersect precisely with the practice of jihad in the early days of Islam. So that a concrete moral ideal is found from these verses that war may be carried out in an emergency. When jihad cannot be diverted from the meaning of war, meaning that Muslims are forced to fight against injustice in order to defend religion, they must fulfill the codes of ethics in war. Meanwhile, from the transcendental side, the moral ideal of the verse is to get closer to Allah by maintaining continuous worship until the end of life. In addition, another moral ideal is that jihad can be achieved by spending money in the way of Allah and endeavoring and trusting solely in Him.